PROGRAMA SEGURO-DESEMPREGO: o desafio para equilibrar proteção social e eficiência econômica - Moisés Villamil Balestro; Danilo Cortes Nolasco Marinho (Revista de Políticas Públicas, 2010)
The purpose of this paper is to analyze the condition in which the Unemployment Insurance Program can combine social protection with a more efficient functioning of the labor market. The program consists of three pillars; unemployment insurance, public employment service and professional and social qualification. In this sense, the Unemployment Insurance Program combines passive (the social benefit payment) and active employment policies (workforce training and employment service). The great challenge for the employment policy is the integration of these three pillars. The data for the elaboration of this paper were drawn from a national research evaluating the Unemplyment Insurance Program.